Diary of a wimpy kid 1, 2 & 3 [videorecording (Blu-Ray)]. - Freudenthal, Thor; Bowers, David, 1970-; Jacobson, Nina; Simpson, Brad, 1973-; Filgo, Jackie; Filgo, Jeff; Sachs, Gabe; Judah, Jeff; Forbes, Maya; Wolodarsky, Wallace; Gordon, Zachary, 1998-; Capron, Robert, 1998-; et al. (20th Century Fox Home Entertainment, 2016)
The world's wimpiest kid tries to survive the hilarious humiliation of middle school in these three films based on Jeff Kinney's best-selling books.